2005
DOI: 10.1097/01.mlg.0000175075.69706.64
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the Oropharynx: Factors Affecting Outcome

Abstract: Patient-related factors such as age and gender were not significant in predicting disease-specific outcome. Important tumor-related factors were the American Joint Committee on Cancer stage and the T stage. Among the oropharyngeal subsites, squamous cell carcinoma of the base of tongue was associated with the worst outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 21 publications
2
23
0
10
Order By: Relevance
“…The literature reported a 40% rate of regional metastases of palate OSCC at the time of the diagnosis (19). Moreover, a study about the main factors related to oropharyngeal carcinoma (base of tongue, uvula, tonsils and palate) found that most injuries on the palate progress to stage III and IV of the TNM system, suggesting high aggressiveness of these tumors (20).…”
Section: Discussionmentioning
confidence: 99%
“…The literature reported a 40% rate of regional metastases of palate OSCC at the time of the diagnosis (19). Moreover, a study about the main factors related to oropharyngeal carcinoma (base of tongue, uvula, tonsils and palate) found that most injuries on the palate progress to stage III and IV of the TNM system, suggesting high aggressiveness of these tumors (20).…”
Section: Discussionmentioning
confidence: 99%
“…When we turn to case series in the literature, we can appreciate ethanol as having a significant role in the development of this disease. Sundaram et al [9] published 61.9% of their patients drinking alcohol in excess of two drinks/day and 69.8% with smoking history of over ten pack years. Gorsky et al [7] series reports 58% of the patients drinking in excess of 4 'drinks' daily and 79% smoking with 35% in excess of 20 cigarettes per day.…”
Section: Aetiologymentioning
confidence: 97%
“…Se sabe que estas sustancias son carcinógenos en pacientes de edad avanzada, también puede estar relacionado con la etiología de CEC en los jóvenes. Junto a esto, el bajo nivel educativo y grupo socioeconómico también se propone como factores de riesgo (Rocha et al;Sundaram et al;Llewellyn et al, 2004).…”
Section: Introductionunclassified
“…Se sabe que estas sustancias son carcinógenos en pacientes de edad avanzada, también puede estar relacionado con la etiología de CEC en los jóvenes. Junto a esto, el bajo nivel educativo y grupo socioeconómico también se propone como factores de riesgo (Rocha et al;Sundaram et al;Llewellyn et al, 2004).Es probable que se requiera más de un factor para producir la malignidad. Los factores extrínsecos tales como el tabaquismo, el alcohol, la luz solar y los factores intrínse-cos incluyen la desnutrición, la anemia y la herencia, incluso son los más citados (Chrcanovic et al, 2010).…”
unclassified
See 1 more Smart Citation